Construting stable 2 × 2 tunnel-structured K1.28Ti8O16@N-doped carbon nanofibers for ultralong cycling sodium-ion batteries. (1st January 2022) - Chen, Xinxiang; Liu, Huiqun; Zhou, Mingzhe; Fang, Guozhao; Zhang, Haimin; Cai, Zhenyang; Zhao, Xiaojun; Xiao, Lairong; Liu, Sainan; Zhang, Yi
Highlights: A novel 2 × 2 tunnel-structured K1.28 Ti8 O16 @N-doped carbon nanofibers are prepared. The electrode exhibits excellent long cycle performance. ABSTRACT: Sodium-ion batteries (SIBs) are one of the most potential candidates for large-scale energy storage due to the low cost and eco-friendliness, however, a stable and reversible anode is urgently developed. In this work, a novel 2 × 2 tunnel-structured K1.28 Ti8 O16 @N-doped carbon nanofibers (KTO@NCNFs) anode is successfully synthesized via simple electrospinning and subsequent thermal treatment with urea acted as the additional convenient nitrogen source. In-situ X-ray diffraction (XRD) measurement confirms the intercalation reaction mechanism and robust structure during Na + insertion/extraction. This composite material exhibits a reversible capacity of 116.4 mAh g   −   1 at a current density of 100 mA g   −   1 after 1000 cycles. More impressively, even at a high current density of 1 A g   −   1, the battery delivers capacity retention of 98.4 mAh g   −   1 after 5000 cycles. The excellent electrochemical performance is attributed to the adequate 2 × 2 tunnel structure and the nano-confinement of N-doped nanofibers on K1.28 Ti8 O16 nanocrystals, which offers enough diffusion paths and enhance the ionic diffusion of sodium ions. This work provides a facile strategy to synthesis stable, reversible, and long-cycle anode for sodium-ion batteries. Graphical abstract: Image, graphical abstract